Determining the seasonal relationships between upstream flows and channel transmission losses along a dryland river reach. (25th August 2022) - Mujere, Never; Mazvimavi, Dominic; Masocha, Mhosisi; Makurira, Hodson
River transmission loss is the reduced amount of flow at downstream locations along a channel due to infiltration into the riverbed and riverbank, evaporation from water surface, transpiration by riparian vegetation and, temporary storage in the river and flood plains. Transmission losses reduce flood stage, recharge local and regional aquifers and, are main sources of groundwater recharge in dryland areas. This study determines the seasonal relationships between upstream flows and channel transmission losses along a river reach in Runde River catchment in Zimbabwe. Using regression equations, channel transmission loss volumes were modelled as the response variables while upstream flow volumes were the predictor variables. The study shows significant (p = 0.000) positive linear relationships between reach upstream flow and transmission loss during the cool, hot and rainy seasons. Also, during the post rainy season, a significant (p = 0.000) power relationship exist between reach upstream flow and transmission loss. This simple approach helps to understand water balances and transmission losses in data scarce dryland river systems.